CASE BASED REASONING FOR HANDLING FINAL STUDENT GRADUATION PROBLEMS AT STMIK PELITA NUSANTARA - Petti Indrayati Sijabat; Endra AP Marpaung (INFOKUM, 2021)
Handling the graduation of problematic final students at STMIK Pelita Nusantara is very much needed during this pandemic considering the problems that were passed in 2020 and many students did not graduate on time due to many problems such as academic problems, study programs and finances. The number of problematic final student problems is caused by quite a number of cases. Examples are students who do not attend lectures according to the curriculum schedule that should be followed, including non-active students for several semesters, students who fail to exceed the minimum standards set by the study program, students do not pay tuition administration fees and students do not know or are not active to get good information academically. and students do not complete the thesis within the stipulated time. The problem is that many students do not graduate on time due to many problems such as academic problems, study programs and finances. This problem is like a student who does not attend lectures for 1 year but can still continue his lectures which happened in the final semester. From the research conducted, it is expected to produce a decision support system that is able to become a medium of information for students and study programs to disseminate information on academic sanctions for students who commit violations